Development of Students’ Worksheet based on Problem Based Learning with Game Based Learning And Pacu Jalur In Bouyance Force - Perdana, Riki; Riwayani, Riwayani; Haroky, Faruq; Eveline, Erlin (PILLAR OF PHYSICS EDUCATION, 2023)
Indonesian local wisdom-based learning still needs to be improved, such as Pacu Jalur. This is useful for introducing the nation's culture to students, so they are not forgotten. However, learning local wisdom must also be integrated with technology-based learning so that it remains in line with current developments. The purpose of this research is to develop students' worksheets for Game-based PBL models integrated with Local Wisdom Pacu Jalur in physics learning. The topic chosen in this study is Bouyance Force. The method in this study uses the 4D model, namely Define, Design, Develop, and Disseminate. The developed students' worksheets have been validated by three physics education lecturers. The research results obtained are aspects of content eligibility 85 (decent), presentation 90 (very feasible), appearance 88 (very feasible), and language 89 very feasible. Based on these findings, it can be concluded that the students' worksheets developed are feasible and ready to be implemented in physics learning on the topic of bouyance force. The recommendation for further research is to test students' worksheets in large-scale learning in physics classes.